Implementation of Administrative Sanctions for Violations of the Prohibition on Giving Money and Goods to Vagrants and Beggars in the Special Region of Yogyakarta - Muhammad Yusrizal; Lego Karjoko (Dinasti Research, 2026)
This study aims to analyze the application of administrative sanctions in law enforcement against violations of the prohibition on giving money and goods to homeless people and beggars in the Special Region of Yogyakarta from the perspective of state administrative law. This study uses a normative legal research method (juridical normative) with a statutory approach and a conceptual approach. The results of the study indicate that the application of administrative sanctions against violations of the prohibition on giving money and goods is an instrument of social control that falls under the authority of the regional government as a form of government coercion (bestuursdwang). The applied administrative sanctions, such as verbal warnings, written warnings, and other administrative actions, aim to foster public legal compliance and support the effectiveness of social development and rehabilitation programs. However, the effectiveness of the implementation of these sanctions still faces various obstacles, including low public legal awareness, strong social empathy values ​​that encourage violations, limited apparatus resources, and weak coordination between related agencies. In addition, the validity of administrative actions is highly dependent on the apparatus' compliance with the General Principles of Good Governance (AUPB), especially the principles of legal certainty, proportionality, and accuracy.